2023
DOI: 10.3390/ijms241612972
|View full text |Cite
|
Sign up to set email alerts
|

Petiveria alliacea Reduces Tumor Burden and Metastasis and Regulates the Peripheral Immune Response in a Murine Myeloid Leukemia Model

Natalia Murillo,
Paola Lasso,
Claudia Urueña
et al.

Abstract: The poor response, adverse effects and drug resistance to treatment of acute myeloid leukemia (AML) have led to searching for safer and more effective therapeutic alternatives. We previously demonstrated that the alcoholic extract of Petiveria alliacea (Esperanza) has a significant in vitro antitumor effect on other tumor cells and also the ability to regulate energy metabolism. We evaluated the effect of the Esperanza extract in vitro and in vivo in a murine model of AML with DA-3/ER-GM cells. First, a chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Notably, it has been documented that the inhibition of glycolysis can lead to elevated glucose levels [28][29][30]. We previously showed a reduction in glycolysis in a breast cancer cellular model (4T1) and an in vivo leukemia model [18,21]. This reduction can be attributed to the primary compounds previously reported in the extract, such as isoleucine and valine, which have shown the ability to decrease proliferation and tumor growth by upregulating the tumor suppressor gene PTEN.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Notably, it has been documented that the inhibition of glycolysis can lead to elevated glucose levels [28][29][30]. We previously showed a reduction in glycolysis in a breast cancer cellular model (4T1) and an in vivo leukemia model [18,21]. This reduction can be attributed to the primary compounds previously reported in the extract, such as isoleucine and valine, which have shown the ability to decrease proliferation and tumor growth by upregulating the tumor suppressor gene PTEN.…”
Section: Discussionmentioning
confidence: 79%
“…Previously, the role of P. alliacea in mitochondrial function was demonstrated, mediated by an ethyl acetate fraction which, in vitro, induces apoptosis in 4T1 cells, activates caspase 3, and causes DNA fragmentation [16,18]. It is also worth noting that an additional impact on mitochondria possibly induced by malic acid has been previously described with the Esperanza extract [21]. Malic acid is known to inhibit succinate dehydrogenase, an enzyme that plays a central role in the TCA cycle and as part of complex II in the electron transport chain [35].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we collected 150 phytocompounds for Petiveria alliacea L. through a systematic literature review [24,[30][31][32][33] and using the online database IMPPAT 2.0 [34] (https://cb.imsc.res.in/imppat/home, accessed on 10 January 2024). The 3D structure of these phytocompounds was extracted from the PubChem database [35].…”
Section: Phytocompound Collection and Preparationmentioning
confidence: 99%
“…Several studies have examined the anti-carcinogenic effects of their essential oils, in the case of L. alba, research has shown its potential in halting the cell cycle and inducing apoptosis in liver and lung cancer cells [14], colon and prostate cancer cells [15], leukemia cells [16], and gastric carcinoma cells [17]. Similarly, P. alliacea has been found to trigger cell apoptosis and reduce the growth capability of breast cancer cell colonies [18], along with diminishing tumor burden and myeloid leukemia metastasis [19]. Despite the significance of these plants and the evidence suggesting that the interaction between medicinal plants and the microbiome results in the production of phytotherapeutic compounds [20][21][22], no studies have been conducted on the microbiome associated with L. alba and P. alliacea.…”
Section: Introductionmentioning
confidence: 99%